Corporate governance and leadership from an Islamic perspective - Khaliq, Ahmad (Science Publishing Corporation, 2018)
The focus on the study of management so far has been mainly on two elements- work (production) and workers’ welfare. Hence the management as well as leadership grid has evolved over years based on these two. Experts did not spare a thought that human is also a spiritual being. Western institutions very recently realized a missing element of spirituality from literature on management. Thus in today’s governance, a good corporate leadership seems to be in short supply due to the lack of spirited executives. The leadership development faces two ways of tackling today’s corporate governance problem. First, one can do more of the same. Second, one can try something different. The Islamic perspective to governance and leadership is interesting not because it is new, but because it worked in the past. This paper intends to rediscover this missing spiritual heritage while presenting it within the framework of up to date knowledge on management, leadership and corporate governance. In this paper I conclude therefore to try to demonstrate that Islamic leadership is possible for all. This is equally good, especially Muslims academic and management practitioners including for non-Muslims alike.